Trade‐offs in soil carbon protection mechanisms under aerobic and anaerobic conditions. (17th April 2020) - Huang, Wenjuan; Ye, Chenglong; Hockaday, William C.; Hall, Steven J.
Abstract: Oxygen (O2 ) limitation is generally understood to suppress oil carbon (C) decomposition and is a key mechanism impacting terrestrial C stocks under global change. Yet, O2 limitation may differentially impact kinetic or thermodynamic versus physicochemical C protection mechanisms, challenging our understanding of how soil C may respond to climate‐mediated changes in O2 dynamics. Although O2 limitation may suppress decomposition of new litter C inputs, release of physicochemically protected C due to iron (Fe) reduction could potentially sustain soil C losses. To test this trade‐off, we incubated two disparate upland soils that experience periodic O2 limitation—a tropical rainforest Oxisol and a temperate cropland Mollisol—with added litter under either aerobic (control) or anaerobic conditions for 1 year. Anoxia suppressed total C loss by 27% in the Oxisol and by 41% in the Mollisol relative to the control, mainly due to the decrease in litter‐C decomposition. However, anoxia sustained or even increased decomposition of native soil‐C (11.0% vs. 12.4% in the control for the Oxisol and 12.5% vs. 5.3% in the control for the Mollisol, in terms of initial soil C mass), and it stimulated losses of metal‐ or mineral‐associated C. Solid‐state 13 C nuclear magnetic resonance spectroscopy demonstrated that anaerobic conditions decreased protein‐derived C but increased lignin‐ and carbohydrate‐C relative to the control. Our results indicate a trade‐off between physicochemical and kinetic/thermodynamic C protection mechanisms under anaerobic conditions, whereby decreased decomposition of litter C was compensated by more extensive loss of mineral‐associated soil C in both soils. This challenges the common assumption that anoxia inherently protects soil C and illustrates the vulnerability of mineral‐associated C under anaerobic events characteristic of a warmer and wetter future climate. Abstract : Humid soils experience periodic oxygen deficiency, which are commonly understood to suppress organic matter decomposition. Incubating soils from a tropical forest and temperate cropland, we found that oxygen limitation suppressed decomposition of new litter but stimulated decomposition of existing organic matter by releasing it from mineral protection. These contrasting mechanisms altered the amount and chemistry of organic matter. Soil carbon losses may be sustained under periodic oxygen limitation, challenging our understanding of climate feedbacks under wetter and warmer future conditions.